I have having trouble finding the derivative of log base 10 times (x/x-1)
The easiest way is to simplify it by using property of logs: log(a/b) = log(a) - log(b)
-->
log₁₀( x / (x - 1) ) = log₁₀(x) - log₁₀(x - 1)
--> convert to natural log, recal log_a(x) = log_b(x) / log_b(a)
log₁₀(x/(x - 1) = { ln(x) - ln(x - 1) } / ln(10)
--> so the derivative is easy now for both (just multiply by 1/ln(10) and subtract)
{ 1/x - 1/(x - 1) } / ln(10)
--> which is
(x - 1 - x) / { x(x - 1)ln(10) } = -1 / (ln(10) * x(x - 1) }
Edit:
If you don't do that simplification first, you still get the same value, but you have to use the chain rule:
log₁₀(x/(x - 1)) = ln(x/(x - 1)) / ln(10)
--> derivative of inside, use quotient rule
{ (x - 1) - x } / (x - 1)² = -1/(x - 1)²
--> now multiply by reciprocal (derivative of natural log):
(x - 1) / x * -1/(x - 1)² = -1 / (x(x - 1))
--> now just divide by the ln(10) and you have the same thing as above
"log base 10 times (x/x-1)" doesn't make sense
1/((x - x^2) Log[10])
First rewrite as log(x)-log(x-1)
differentiate one term at a time
y=logx<->10^y=x
yln10=lnx
y=lnx/ln10
dy/dx=1/xln10
y=log(x-1)
10^y=x-1
yln10=ln(x-1)
y=ln(x-1)/ln10
dy/dx=1/(x-1)ln10
Final Answer
dy/dx=1/xln10-1/(x-1)ln10
Copyright © 2024 Q2A.ES - All rights reserved.
Answers & Comments
Verified answer
The easiest way is to simplify it by using property of logs: log(a/b) = log(a) - log(b)
-->
log₁₀( x / (x - 1) ) = log₁₀(x) - log₁₀(x - 1)
--> convert to natural log, recal log_a(x) = log_b(x) / log_b(a)
log₁₀(x/(x - 1) = { ln(x) - ln(x - 1) } / ln(10)
--> so the derivative is easy now for both (just multiply by 1/ln(10) and subtract)
{ 1/x - 1/(x - 1) } / ln(10)
--> which is
(x - 1 - x) / { x(x - 1)ln(10) } = -1 / (ln(10) * x(x - 1) }
Edit:
If you don't do that simplification first, you still get the same value, but you have to use the chain rule:
log₁₀(x/(x - 1)) = ln(x/(x - 1)) / ln(10)
--> derivative of inside, use quotient rule
{ (x - 1) - x } / (x - 1)² = -1/(x - 1)²
--> now multiply by reciprocal (derivative of natural log):
(x - 1) / x * -1/(x - 1)² = -1 / (x(x - 1))
--> now just divide by the ln(10) and you have the same thing as above
"log base 10 times (x/x-1)" doesn't make sense
1/((x - x^2) Log[10])
First rewrite as log(x)-log(x-1)
differentiate one term at a time
y=logx<->10^y=x
yln10=lnx
y=lnx/ln10
dy/dx=1/xln10
y=log(x-1)
10^y=x-1
yln10=ln(x-1)
y=ln(x-1)/ln10
dy/dx=1/(x-1)ln10
Final Answer
dy/dx=1/xln10-1/(x-1)ln10